UiTM Melaka welcomes Spanish Ambassador for cross-cultural teaching session - UiTM, UiTM Global (Office of International Affairs (OIA), 2025)
On 20 June 2025, His Excellency Jose Luis Pardo Cuerdo. The Ambassador of Spain presented an online a session on Collaborative Teaching for Geography and Culture in Tourism. The session was hosted by UiTM Melaka in collaboration with the Embassy of Spain with the aim to foster cross-cultural academic exchange and promote global perspectives in education. The session featured insightful discussions led by the Ambassador. focusing on Spain's educational landscape, cultural heritage. and opportunities for academic collaboration. Students and faculty members benefited from the enriching dialogue, which not only deepened their understanding of international relations but also opened doors for future partnerships in teaching, research. and mobility programs.